Experiences of persons with spinal cord injury undertaking a physical activity programme as part of the SCIPA 'Full-On' randomized controlled trial. Issue 2 (April 2018) - Calder, Allyson; Nunnerley, Jo; Mulligan, Hilda; Ahmad Ali, Nordawama; Kensington, Gemma; McVicar, Tim; van Schaik, Olivia
Abstract: Background: For individuals with spinal cord injury the long term benefits of physical activity are well documented, however the majority of this population report inactivity secondary to participatory barriers. Research investigating physically intensive exercise programs for people with spinal cord injury is limited, with even less attention paid to the experience of the participants. Objective: To explore the experiences of persons with spinal cord injury of their participation in the New Zealand arm of the Spinal Cord Injury and Physical Activity (SCIPA) 'Full-On' randomized controlled trial. Method: Eight participants recruited to SCIPA Full-On completed individual virtual video diary interviews three times across the duration of their twelve week Full-On trial. Expectations and highs and lows of the program were recorded via a webcam. The video diary data were transcribed verbatim and analyzed inductively for themes. Results: Three independent themes were identified from the data: the participants' excitement of opportunity to participate in SCIPA Full-On' randomized controlled trial, personal rewards from participation and also the frustrations to participation they experienced. Conclusion: This study provides valuable information on factors that motivate participation in physical activity for individuals with spinal cord injury, within a research setting. The findings highlighted the importance of accessibility and a supportive network which may be a way to provide individuals with spinal cord injury the means to become self-efficacious to participate in community physical activity outside of the research environment.